(untitled) (Al-Academy, 2017)
This paper deals with the role of the clergy in the Church and artists in the emergence of this art, which is represented by an atmosphere of spiritual, aesthetic, artistic, technical and engineering very magnificence and is located in two Find.Chapter One: the stages of stained glass in the Middle AgesThe Architects Goths to get rid of the walls gradually, based Baloctav plane, columns and beams strengthened with the vehicle, as previously mentioned, making the building looks like a glass of excessive use of colored windows building, this art has been known to the art of stained glass And the second chapter: the stages of stained glass in the Middle Ages Department of Winston (Winston) works of stained glass since its inception in the tenth century to the Renaissance into three main stages:Each of these stages characteristics distinguish them, and show architectural style,The first stage: the English and called early, and start this stage since the inception of stained glass until the thirteenth century.Phase II: called ornate style in the fourteenth century.The third stage: is called a phase-based glass that separates the Middle Ages (the art of stained glass) for the Renaissance located this stage in the fifteenth century.And between each of these stages a very short period of transition does not Taataada ten years